2000
DOI: 10.1097/00001648-200011000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Tanner Stage in Girls Exposed In Utero and Postnatally to Polybrominated Biphenyl

Abstract: Accidental contamination of the Michigan food chain with polybrominated biphenyls (PBBs) led to the exposure of more than 4,000 individuals in 1973. Because PBB exposure is suspected to disrupt endocrine function, we assessed pubertal development in females 5-24 years of age (N = 327) who were exposed to PBB in utero and, in many cases, through breastfeeding. We estimated in utero PBB exposure using maternal serum PBB measurements taken after exposure (1976-1979) and extrapolated to time of pregnancy using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(194 citation statements)
references
References 40 publications
8
181
1
4
Order By: Relevance
“…Delayed initiation of breast development was found in girls with higher prenatal dioxin exposure . In several other studies, no significant association was found between exposure to persistent chlorinated compounds and timing of puberty, in girls (Blanck et al, 2000;Gladen et al, 2000;Vasiliu et al, 2004) or in boys (Gladen et al, 2000;Mol et al, 2002).…”
Section: Discussionmentioning
confidence: 70%
“…Delayed initiation of breast development was found in girls with higher prenatal dioxin exposure . In several other studies, no significant association was found between exposure to persistent chlorinated compounds and timing of puberty, in girls (Blanck et al, 2000;Gladen et al, 2000;Vasiliu et al, 2004) or in boys (Gladen et al, 2000;Mol et al, 2002).…”
Section: Discussionmentioning
confidence: 70%
“…Menarche and pubic hair, but not breast development, appeared earlier in breastfed girls exposed to high polybrominated biphenyl levels in utero, than those with low exposure in utero or those not breastfed (Blanck et al, 2000). Prenatal exposure to persistent organochlorine pollutants via maternal fish consumption was not associated with age at menarche (Axmon, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Among breast-fed girls, those with higher prenatal exposure to PBB reached menarche at 11.6 years, whereas those with lower PBB exposure did so at 12.2 years. Girls who had been formula fed reached menarche at 12.7 years and their PBB exposure had no effect (Blanck et al, 2000).…”
Section: Adolescent Growth and Sexual Maturationmentioning
confidence: 96%